2021
DOI: 10.1109/access.2021.3068964
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle Trajectory Reconstruction on Urban Traffic Network Using Automatic License Plate Recognition Data

Abstract: Vehicle trajectory data are critical to urban active traffic management and simulation applications. Automatic license plate recognition (ALPR) data can provide partial vehicle trajectory information by matching the detected vehicle license plates through time series. However, the trajectory extracted from ALPR data tend to be sparse and incomplete due to technical and financial constraints. This paper deals with the problem of sparse trajectory reconstruction based on ALPR data. Firstly, the multiple travel a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The upper and lower tolerance line settings for distinguishing between normal and abnormal severity levels come from network operation and maintenance experience, management requirements, or device capacity limitations, and the accuracy of the settings determines whether the algorithm can work. Excessive tightness (such as a small upper limit value or a large lower limit value) may lead to false positives [6,15]; Excessive looseness (such as high upper limit values and low lower limit values) may lead to false positives, increase the workload of monitoring personnel, affect the enthusiasm of maintenance personnel, and ultimately reduce the effectiveness of this technology. At the same time, as the number of indicators, network elements, and business systems included in the active monitoring scope increases, the number of upper and lower tolerance lines that need to be set will also increase sharply, indicating a practical need to improve work efficiency.…”
Section: Static Baseline Algorithmmentioning
confidence: 99%
“…The upper and lower tolerance line settings for distinguishing between normal and abnormal severity levels come from network operation and maintenance experience, management requirements, or device capacity limitations, and the accuracy of the settings determines whether the algorithm can work. Excessive tightness (such as a small upper limit value or a large lower limit value) may lead to false positives [6,15]; Excessive looseness (such as high upper limit values and low lower limit values) may lead to false positives, increase the workload of monitoring personnel, affect the enthusiasm of maintenance personnel, and ultimately reduce the effectiveness of this technology. At the same time, as the number of indicators, network elements, and business systems included in the active monitoring scope increases, the number of upper and lower tolerance lines that need to be set will also increase sharply, indicating a practical need to improve work efficiency.…”
Section: Static Baseline Algorithmmentioning
confidence: 99%
“…These fall into two main categories: studies that have attempted to create trajectories of the entire trip of the vehicle through a network, and those that have focused on a finer path resolution within a single link. In general, trajectories running across the entire network do not have the resolution necessary to calculate acceleration and deceleration accurately and are instead often used for large-scale travel time estimates ( 42 ). Li et al found that trajectories created for a single link can be more accurate, though the methodology for speed estimation is critical ( 43 ).…”
Section: Introductionmentioning
confidence: 99%
“…Accurate and reliable vehicle trajectory data are significant in the intelligent transportation system and urban traffic management [1]. Trajectory data provide a rich source of information for many application areas, such as getting onsite speed, queue, delay, acceleration, and driving time [2].…”
Section: Introductionmentioning
confidence: 99%